Odpowiedź :
Odpowiedź:
a) 15x-47 = 3x+37
15x-3x = 37+47
12x = 84 |:12
x = 7
b) 5x+12 = 9x-16
5x-9x = -16-12
-4x = -28 |:(-4)
x = 7
c) -12+x = 30+3x
x-3x = 30+12
-2x = 42 |:(-2)
x = -21
d) 24-6x = -2x-12
-6x+2x = -12-24
-4x = -36 |:(-4)
x = 9
e) 3-3x = 2x-7
-3x-2x = -7-3
-5x = -10 |:(-5)
x = 2
Proszę :)
Szczegółowe wyjaśnienie:
Odpowiedź:
15x – 47 = 3x + 37
15x-3x=37+47
12x=84 /:12
x=7
b) 5x + 12 = 9x – 16
5x-9x=-16-12
-4x=-28 /:(-4)
x=7
c) -12 + x = 30 + 3x
x-3x=30+12
-2x=42 /:(-2)
x=-21
d) 24 – 6x = -2x – 12
-6x+2x=-12-24
-4x=-36 /:(-4)
x=9
e) 3 – 3x = 2x – 7
-3x-2x=-7-3
-5x=-10 /:(-5)
x=2
Szczegółowe wyjaśnienie: